Pengaruh Return on Assets, Leverage, dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Fernando Eryanto; Fung Jin Tjhai (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This research aimed to analyze the effect of return on assets, leverage, firm size, sales growth, business strategy, and investment decisions on tax avoidance. The research samples were manufacturing companies listed on the Indonesia Stock Exchange (IDX) over three-year period, from 2022 to 2024. These companies were selected using a purposive sampling method, and 99 companies met the criteria or a total of 297 data. The data were analyzed using multiple regression. The results showed return on assets and sales growth positively influence tax avoidance. The higher a company's profit and sales growth, the greater its tendency to engage in tax avoidance. Meanwhile, firm size negatively influences tax avoidance. Larger companies are more compliant with tax obligations because they prioritize public image and reputation. Leverage, business strategy, and investment decisions have no effect on tax avoidance. The results of this research provided important theoretical and practical implications. Theoretical implication was provided by demonstrating the difference between taxes paid by companies and the tax rate according to the tax regulations, where companies achieving higher profits and sales growth will engage in tax avoidance to reduce the taxes paid. Practically, companies are expected to improve their tax compliance by not engaging in tax avoidance, while the regulator or government can increase oversight of companies through tax regulations. Furthermore, investors are advised to focus more on company size when making investment decisions because larger companies are more compliant with tax obligations.